ETHICAL LEADERSHIP, MANAGERIAL TRUST, AND PSYCHOLOGICAL WELL-BEING AS DRIVERS OF ORGANIZATIONS - Joevy Ageng Firmansyach; Fatmah Bagis; Tri Septin Muji Rahayu; Suyoto (JURNAL ILMIAH EDUNOMIKA, 2026)
In the ever-changing education sector, employee extra-role behavior has become a crucial element for organizational sustainability. This study aims to examine the effect of ethical leadership on Organizational Citizenship Behavior (OCB) by involving trust in management and psychological well-being as mediating variables. Using a quantitative approach and replication design, this study was conducted among employees of Islamic Educational Institutions in Cilacap Regency through a survey of 225 respondents selected using purposive sampling. Data processing was carried out using SEM-PLS to test the direct and indirect relationships between variables. The results show that ethical leadership has a positive influence on OCB, and this influence is strengthened through the role of trust in management and psychological well-being. These findings confirm that leaders who act as moral role models can build trust, create healthier psychological conditions, and ultimately encourage employee prosocial behavior. Practically, this study recommends strengthening an ethical leadership culture, increasing transparent communication, and programs that support psychological well-being to foster sustainable OCB. Furthermore, further research is recommended to expand the context and add other variables that influence the dynamics of work behavior.